A coupling technique for non-matching finite element meshes - Bitencourt, Luis A. G.; Manzoli, Osvaldo L. [UNESP]; Prazeres, Plinio G. C.; Rodrigues, Eduardo A.; Bittencourt, Tulio N. (Elsevier B.V., 2015)
This paper presents a novel technique for coupling non-matching finite element meshes, based on the use of special finite elements termed coupling finite elements (CFEs), which share nodes with non-matching meshes. The main features of the proposed technique are: (i) no additional degree of freedom is introduced to the problem; (ii) non-rigid coupling can be considered to describe the nonlinear behavior of interfaces similar to cohesive models; (iii) non-matching meshes of any dimension and any type of finite elements can be coupled, and (iv) overlapping and non-overlapping meshes can be considered. The applicability of the proposed technique is illustrated by a variety of 2D and 3D examples with different non-matching mesh configurations. The results demonstrate that the technique is able to enforce the continuity of displacements in the case of rigid coupling, and to properly transfer the interaction forces across the non-matching interfaces, according to any chosen interface model, in the case of non-rigid coupling. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Finite elements; Non-matching meshes; Coupling scheme; Interface model; Multiscale analysis